Balancing preservation and energy efficiency in building stocks. Issue 2 (29th October 2019) - Eriksson, Petra; Milić, Vlatko; Brostrom, Tor
Abstract : Purpose: Energy use in buildings needs to be reduced to meet political goals; however, reducing energy use can conflict with heritage preservation objectives. The purpose of this paper is to demonstrate a method that combines quantitative and qualitative analyses of the potential of energy savings in an historic building stock. Specifically, this study examines how requirements of historic building preservation affect the energy saving potential on a building stock level. Design/methodology/approach: Using the World Heritage Town of Visby, Sweden as a case study, this paper illustrates a step-by-step method as a basis for implementing energy savings techniques in an historic building stock. The method contains the following steps: categorisation of a building stock, definition of restriction levels for energy renovation scenarios and life cycle costs optimisation of energy measures in archetype buildings representing the building stock. Finally, this study analyses how different energy renovation strategies will impact heritage values and energy saving potentials for different categories of buildings. Findings: The outcome of the study is twofold: first, the method has been tested and proven useful and second, the results from the application of the method have been used to formulate differentiated energy renovation strategies for the case study. Originality/value: The study shows that it is possible to integrate techno-economic analysis with assessment of heritage values in a given building stock in order to facilitate a strategic discussion balancing policies and targets for energy savings with policies for the preservation of heritage values. The findings will contribute to sounder policy development and planning for historic building stocks.